Improved efficacy of mesenchymal stromal cells stably expressing CXCR4 and IL-10 in a xenogeneic graft versus host disease mouse model - Hervás-Salcedo, Rosario; Fernández-García, María; Hernando-Rodríguez, Miriam; Suárez-Cabrera, Cristian; Bueren, Juan A.; Yáñez, Rosa M. (Frontiers in Immunology, 2023)
Previous clinical trials have shown that mesenchymal stromal cells (MSCs) can modulate graft versus host disease (GvHD) after allogeneic hematopoietic transplantation, although with variable efficacy. To improve the anti-GvHD effect of these cells, adipose tissue derived-human MSCs (Ad-MSCs) were transduced with a lentiviral vector conferring stable expression of CXCR4, a molecule involved in cell migration to inflamed sites, and IL-10, a cytokine with potent anti-inflammatory properties. In vitro experiments showed that the expression of these molecules in Ad-MSCs (named CXCR4-IL10-MSCs) efficiently enhanced their migration towards SDF-1α and also improved their immunomodulatory properties compared to unmodified Ad-MSCs (WT-MSCs). Moreover, using a humanized GvHD mouse model, CXCR4-IL10-MSCs showed improved therapeutic effects, which were confirmed by histopathologic analysis in the target organs. Additionally, compared to WT-MSCs, CXCR4-IL10-MSCs induced a more marked reduction in the number of pro-inflammatory Th1 and Th17 cells, a higher polarization towards an anti-inflammatory T cell profile (CD3+-IL10+ cells), and increased the number of regulatory T and B cells. Our in vitro and in vivo studies strongly suggest that CXCR4-IL10-MSCs should constitute an important new generation of MSCs for the treatment of GvHD in patients transplanted with allogeneic hematopoietic grafts.